Crystal structure of human calcineurin complexed with cyclosporin A and human cyclophilin - Jin, Lei (National Academy of Sciences, 2002)
Calcineurin (Cn), a Ca(2+)/calmodulin-dependent Ser/Thr protein phosphatase, is an important participant in signaling pathways that activate T cells. It is the target of the immunosuppressive drugs cyclosporin A (CsA) and FK506. These drugs bind proteins known as cyclophilin (Cyp) and FK506-binding protein, respectively, and the drug–protein complexes in turn inhibit Cn. We report the crystal structure of a Cyp/CsA/Cn ternary complex, determined to a resolution of 3.1 Å. Residues 3–9 of CsA, particularly N-methyl leucines 4 and 6, and Trp-121 of Cyp form a composite surface for interaction with Cn. The hydrophobic interface buries two hydrogen bonds. The structure accounts clearly for the effects of mutations in Cn on CsA-resistance and for the way modifications of CsA alter immunosuppressive activity.